Preschool Teachers' Understanding Level About Stunting Mitigation in The ECE Unit, Samarang District, Garut Regency - Yuliani, Yeni; Puridawaty, Brigita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research uses a quantitative descriptive method with a survey approach. The sampling technique used purposive sampling with 50 Early Childhood Education (ECE) teachers as respondents from 16 ECE institutions in the Samarang District. Questionnaire format The instrument used was a standard instrument that had been tested and used in the GTK ECE DIKLAT Tiered Application training module version 1.0 in accelerating stunting reduction which was published by GTK ECE Kemendikbudristek. Data was collected through questions with 12 answer method questions with a yes score of 1 and a no score of 0 (zero) using a checklist (V) so that the yes and no answers were used to measure the level of understanding. The results of the research show that the level of understanding of ECE teachers regarding stunting mitigation in Samarang District is in the “Low” category at 70% (35 teachers), “Medium” at 30% (15 teachers), ECE teachers with an understanding of stunting mitigation in the “High” category do not exists (ZERO). The average understanding score is 1.8%, indicating that ECE teachers’ understanding of stunting mitigation is “Low”. So it can be concluded that the level of understanding of ECE teachers in Samarang District regarding stunting mitigation is relatively low.